Relations in Indian philosophy - Jha, V. N. (Sri Garib Das oriental series, 1992)
Contributed research papers presented at the National Seminar on Relations in Indian Philosophy, held during 25th-27th March 1991 at the Centre of Advanced Study in Sanskrit, University of Poona.